Altered cerebellar‐cerebral functional connectivity in benign adult familial myoclonic epilepsy. (1st April 2016) - Long, Lili; Zeng, Ling‐Li; Song, Yanmin; Shen, Hui; Fang, Peng; Zhang, Linlin; Xu, Lin; Gong, Jian; Zhang, Yun‐Ci; Zhang, Yong; Zhou, Pinting; Huang, Sha; et al.
Summary: Objective: The pathogenesis of benign adult familial myoclonic epilepsy (BAFME) remains unknown, although cerebellar pathologic changes and brain hyperexcitability have been reported. We used resting‐state functional magnetic resonance imaging (fMRI) to examine the functional connectivity between the cerebellum and cerebrum in a Chinese family with BAFME for the first time. Methods: Eleven adults with BAFME and 15 matched healthy controls underwent resting‐state blood oxygen level–dependent (BOLD) fMRI scanning. The cerebellar seeds, including the bilateral crus I, lobule VIII, lobule VIIb, and lobule IV&V, were defined a priori. Next, regional time courses were obtained for each individual by averaging the BOLD time series over all voxels in each seed region. Then, seed‐based functional connectivity z‐maps were produced by computing Pearson's correlation coefficients (converted to z‐scores by Fisher transformation) between each seed signal and the time series from all other voxels within the entire brain. Finally, a second‐level random‐effect two‐sample t ‐test was performed on the individual z‐maps in a voxel‐wise manner. Results: Reduced functional connectivity of the right cerebellar crus I with the left middle frontal gyrus and right cerebellar lobule IX was observed in the default network of BAFME. Enhanced functional connectivity of the left cerebellar lobule VIII with the bilateral middle temporal gyri, right putamen, and left cerebellar crus I was found in the dorsal attention network of BAFME. Enhanced functional connectivity between the left cerebellar lobule VIIb and right frontal pole was found in the control network of BAFME. Significance: Altered cerebellar‐cerebral functional connectivity may contribute to the understanding of the nosogenesis of BAFME and explain the cognitive dysfunction in this Chinese family with BAFME.